2015
DOI: 10.1016/j.intimp.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

HDAC expression and activity is upregulated in diseased lupus-prone mice

Abstract: Prior studies have shown that pan-HDAC inhibition can decrease disease in lupus mice; however, the mechanisms(s) remain to be elucidated. MRL/MpJ-Faslpr (MRL/lpr) mice develop a lupus-like disease characterized by anti-dsDNA production, lymphoproliferation, and immune complex-mediated glomerulonephritis. Early- and late-disease (12 and 20 weeks-of-age respectively) female MRL/lpr mice were compared to age-matched, healthy C57BL/6 mice for HDAC expression and activity in bone marrow (BM) B cells, splenic B and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 60 publications
(86 reference statements)
1
27
0
Order By: Relevance
“…We are not sure in this study whether HDAC6 inhibition has direct effects on autoreactive B and T cell responses or only indirect effects through down-regulating IFN-a. As one of our previous studies showed that B cells and T cells in another lupus model, Murphy-Roths large lupus-prone mice (MRL/lpr) mice, expressed HDAC6, even at significantly higher levels compared to those in non-lupus mice [17], we speculate that HDAC6 inhibition should have both direct and indirect effects on the alteration of B and T cell responses. To demonstrate this hypothesis, we will create NZB/W mice with pDC-, T cell-and B cell-specific HDAC6 depletion, respectively, in future studies.…”
Section: Hdac6 Inhibition Decreases Lupus Nephritismentioning
confidence: 71%
See 2 more Smart Citations
“…We are not sure in this study whether HDAC6 inhibition has direct effects on autoreactive B and T cell responses or only indirect effects through down-regulating IFN-a. As one of our previous studies showed that B cells and T cells in another lupus model, Murphy-Roths large lupus-prone mice (MRL/lpr) mice, expressed HDAC6, even at significantly higher levels compared to those in non-lupus mice [17], we speculate that HDAC6 inhibition should have both direct and indirect effects on the alteration of B and T cell responses. To demonstrate this hypothesis, we will create NZB/W mice with pDC-, T cell-and B cell-specific HDAC6 depletion, respectively, in future studies.…”
Section: Hdac6 Inhibition Decreases Lupus Nephritismentioning
confidence: 71%
“…Interestingly, lymphocyte development and numbers in these mice are normal, although there is a mild decrease in the immune response after antigenic stimulation [42]. With regard to SLE, we have previously observed increased expression and activity of HDAC6 within B cells, T cells and glomerular cells of diseased lupus-prone mice [17].…”
Section: Hdac6 Inhibition Decreases Lupus Nephritismentioning
confidence: 92%
See 1 more Smart Citation
“…Further animal studies reveal increased HDAC6 expression in T cells and B cells derived from NZB/W mice [69], and inhibition of HDAC6 reduces lupus pathogenesis in NZB/W mice, which suggest a potential role of HDAC6-dependent selective autophagy in SLE pathogenesis. Therapeutic treatments inhibiting autophagy pathway or autophagy-related proteins may improve SLE clinical outcomes by reducing autoreactive lymphocytes differentiation and their associated functions.…”
Section: Autophagy/autophagy-related Proteins In Autoimmune Diseasesmentioning
confidence: 99%
“…Unlike class I HDACs, Class IIa HDACs (HDAC4, 5, 7 and 9) display tissue-specific expression and are involved in a variety of signal transduction pathways [13]. The well-known class IIb HDAC6 controls the status of tubulin and hsp90 acetylation [14]. All these indicates each HDAC enzyme has its unique function in normal cells, therefore, most pan-HDAC inhibitors (HDACIs), which inhibit a broad spectrum of HDACs, exhibited significant toxicity.…”
Section: Introductionmentioning
confidence: 99%